Analysis of the Current State of the Fight Against Climate Change in Bulgaria - Yordanov, Nikolay (Research Papers, 2025)
The purpose of this report is a critical review of the development of the main global legislations aimed at limiting the negative effects of climate change, including the ways of financing the fight against climate change. A comparison is made between the existing legislation in the Republic of Bulgaria and the ratified international climate agreements. Those that should be proven or rejected are that 1) the legislation in the Republic of Bulgaria is harmonized with the world legislation and will help to achieve climate neutrality; 2) the stage of combating climate change, in which the Republic of Bulgaria is currently located, will allow the achievement of climate neutrality goals by 2030 and 2050, respectively. We provide a summary of the development of these topics.